Multiple-Text Manuscripts from the Gondarine Age: MSS London, BL Orient. 818 and Paris, BnF Éth. 146 - Villa, Massimo (Aethiopica, 2021)
It would be ungenerous to claim that the Ethiopian manuscript heritage preserved in major Western libraries, although having been identified and catalogued for decades, has no more surprises in store. Mss BL Or. 818 and BnF Éthiopien 146 are two skilfully executed multiple-text manuscripts which share the same combination of texts, although arranged in a different order. Independent philological surveys have recurrently evidenced a close genetic affinity between the two pieces. Nevertheless, an overall assessment of their history has never been made. A scrutiny of the textual and historical data reveals that the two manuscripts were produced and intended as gifts for the churches of Dabra Ḍaḥāy Qʷǝsqʷām in Gondar and Nārgā Śǝllāse, both established and patronized in the mid-eighteenth century by ʾƎtege Mǝntǝwwāb, mother of ʾAṣe ʾIyāsu II. The present study aims to demonstrate that the two manuscripts are not only outstanding examples of Gondarine bookmaking culture, but also witnesses to a deliberate initiative of production and dissemination of parchment artefacts in favour of ecclesiastical foundations in the area of Lake Ṭānā. Furthermore, independent pieces of evidence from several texts contained in the two codices suggest that MS BnF Éthiopien 146 was most likely copied from MS BL Or. 818.